Experimental investigation on characteristics of algae biodiesel in a diesel engine - Naresh, V.; Prabhakar, S.; Annamalai, K.; Naveenchandran, P. (International Journal of Engineering and Technology, 2018)
The study titled â€œPerformance and Emission Studies on a 4 stroke Diesel Engine Using Methyl Ester of ALGAE Oil with EGRâ€ involves detail investigation of characteristics (performance and emission] of Blends of Methyl Esters of ALGAE oil by varying the EGR control value (5 to 20%] using direct injection diesel engine.From the preceding studies on similar title itâ€™s established that the release of NOX is higher in ALGAE based biodiesel.The focus of this study is about the NOX emission and how it can be reduced by using the cooled EGR.